Vancomycin and Ampicillin Resistance in Enterococcus: A Six Month Study of Urine Cultures at Sheikh Zayed Hospital, Lahore (Journal of Fatima Jinnah Medical University, 2018)
Objective : To study the frequency of Vancomycin and Ampicillin resistance enterococci isolated from urine culture specimens alongwith their antimicrobial susceptibility patterns.Study Design : Retrospective studyPlace and duration of Study : Department of Microbiology, Sheikh Zayed Hospital, Lahore from 1 June to 30 November 2013.Material and Methods : All samples received for urine culture, from which vancomycin- and ampicillin-resistant Enterococci were isolated, were included in the study and an analysis was made of their antimicrobial susceptibility patterns.Results : Out of the 4852 urine samples received for culture, Enterococci were isolated from 172 cases (3.5%). Out of these 172 samples, 30 (17.4 %) were vancomycin- and ampicillin-resistant. All of these 30 strains were sensitive to Linezolid (100%) while nitrofurantoin was sensitive in 16 strains (53.3 %).Conclusion : Enterococci are inherently resistant to several antimicrobials and vancomycin and ampicillin resistance greatly limits the treatment options for such strains. An overview of their susceptibility patterns may help in devising treatment strategies for multi-drug resistant infections.
Keywords: Enterococcus. Vancomycin. Ampicillin. Antimicrobial susceptibility.